2008
DOI: 10.2466/pms.106.2.637-644
|View full text |Cite
|
Sign up to set email alerts
|

Physical Educators' Beliefs about Teaching Children with Disabilities

Abstract: The primary purpose was to extend Rizzo's research and identify the variables which contribute significantly to physical educators' positive beliefs about teaching children with disabilities. The second purpose was to structure physical educators' beliefs by conditions of disability. Participants were a stratified random sample of 168 physical educators, 79 men and 89 women from eastern USA. Responses to Rizzo's Physical Educators' Attitudes Toward Teaching Individuals with Disabilities-III indicated that teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
23

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 13 publications
3
51
1
23
Order By: Relevance
“…Previous studies have revealed equivocal findings, with some of them reporting that experience with students having certain disabilities led to positive attitude formation (e.g., Block & Rizzo, 1995;Obrusnikova, 2008;Özer et al, 2013;Rizzo & Vispoel, 1991), and other studies reporting no such effect (Block & Rizzo, 1995;Rizzo, 1984;Schmidt-Gotz et al, 1994). Most authors who have found supportive evidence for longer acquaintance supported their findings with the Contact Theory (Allport, 1954), which suggests that the amount and type of contact is related to its effect.…”
Section: Previous Acquaintance and Experience With Students With Disamentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have revealed equivocal findings, with some of them reporting that experience with students having certain disabilities led to positive attitude formation (e.g., Block & Rizzo, 1995;Obrusnikova, 2008;Özer et al, 2013;Rizzo & Vispoel, 1991), and other studies reporting no such effect (Block & Rizzo, 1995;Rizzo, 1984;Schmidt-Gotz et al, 1994). Most authors who have found supportive evidence for longer acquaintance supported their findings with the Contact Theory (Allport, 1954), which suggests that the amount and type of contact is related to its effect.…”
Section: Previous Acquaintance and Experience With Students With Disamentioning
confidence: 85%
“…Based on a North American perspective, Obrusnikova (2008) concluded that the beliefs of PE teachers toward teaching children with disabilities were generally positive, but that they varied according to the type of disability. Beliefs were reported to be more favorable toward teaching children with specific learning disabilities and less favorable toward teaching children with emotional and behavioral disorders.…”
Section: Attitudes and Self-efficacy Scoresmentioning
confidence: 99%
“…Otros autores, sin embargo, señalan a los alumnos con problemas de aprendizaje percibidos más positivamente que los alumnos con trastornos emocionales y de conducta (Obrusnikova, 2008;Rizzo y Vispoel, 1991).…”
Section: Variables Relacionadas Con El Alumno (Tipo De Discapacidad unclassified
“…Los resultados obtenidos en estudios realizados en distintos países refuerzan la idea de que los docentes que reciben formación específica para atender a los alumnos con discapacidad tienen reacciones más afectivas y actitudes más favorables que los que no la han recibido (Beh-Pajooh, 1991;Block y Rizzo, 1995;Obrusnikova, 2008), aunque se puedan encontrar otros estudios que no encontraron ninguna correlación significativa entre los cursos de formación y las creencias (Rizzo y Vispoel, 1991;Rizzo y Wright, 1988).…”
Section: Variables Relacionadas Con El Propio Docente (Atributos Y Peunclassified
See 1 more Smart Citation